Propagation phase-contrast micro-computed tomography allows laboratory-based three-dimensional imaging of articular cartilage down to the cellular level. Issue 1 (January 2020) - Clark, J.N.; Garbout, A.; Ferreira, S.A.; Javaheri, B.; Pitsillides, A.A.; Rankin, S.M.; Jeffers, J.R.T.; Hansen, U.
Summary: Objective: High-resolution non-invasive three-dimensional (3D) imaging of chondrocytes in articular cartilage remains elusive. The aim of this study was to explore whether laboratory micro-computed tomography (micro-CT) permits imaging cells within articular cartilage. Design: Bovine osteochondral plugs were prepared four ways: in phosphate-buffered saline (PBS) or 70% ethanol (EtOH), both with or without phosphotungstic acid (PTA) staining. Specimens were imaged with micro-CT following two protocols: 1) absorption contrast (AC) imaging 2) propagation phase-contrast (PPC) imaging. All samples were scanned in liquid. The contrast to noise ratio (C/N) of cellular features quantified scan quality and were statistically analysed. Cellular features resolved by micro-CT were validated by standard histology. Results: The highest quality images were obtained using propagation phase-contrast imaging and PTA-staining in 70% EtOH. Cellular features were also visualised when stained in PBS and unstained in EtOH. Under all conditions PPC resulted in greater contrast than AC ( p  < 0.0001 to p  = 0.038). Simultaneous imaging of cartilage and subchondral bone did not impede image quality. Corresponding features were located in both histology and micro-CT and followed the same distribution with similar density and roundness values. Conclusions: Three-dimensional visualisation and quantification of the chondrocyte population within articular cartilage can be achieved across a field of view of several millimetres using laboratory-based micro-CT. The ability to map chondrocytes in 3D opens possibilities for research in fields from skeletal development through to medical device design and treatment of cartilage degeneration.